Identifying factors that contribute to tertiary level students' speaking anxiety in ESL classroom / Nur Umira Mustapha - Mustapha, Nur Umira (2014)
Learning English as a Second Language is mainly focused on four major skills which are writing,reading,listening and speaking. Among these four major skills, speaking skill is considered as the most difficult skill to excel among the ESL learners. As a result, some of the ESL learners feel anxious when they have to speak in English. This problem was known as speaking anxiety.Speaking anxiety brings impact towards the learning process because it affects the fluency and also the communication process itself. There are many research done to analyze the speaking anxiety issue and to clarify the factors that contribute to speaking anxiety. The aim of this study was to identify the contributing factors affecting speaking anxiety among tertiary level students.This study involved 56 Diploma part one students in UiTM Dungun, Terengganu who have registered for BEL 120 (Consolidating Language Skills) course. A mixed method involved quantitative and qualitative methods was employed. The main instrument used to gather the quantitative data is the FLCAS (Foreign Language Classroom Anxiety Scale) which was adapted from a study done by Horwitz and Cope (1986). In the questionnaire there are 33 items which were divided into 3 factors related to speaking anxiety. The 3 factors which were analysed in this study are the motivation in learning ESL, fear of negative evaluation and English language proficiency. The data gathered were analysed using the SPSS software. For the qualitative data, a semi-structured interview was carried out with five respondents who were randomly selected to triangulate the results of this study. The quantitative data resulted the major factor that affect the speaking anxiety is the fear of negative evaluation. The respondents mentioned that they are not worried of making mistakes but they are particularly concern on the feedback given by their language lecturers especially during the speaking assessment. In addition, to become eloquent speaker there is a need for the ESL learners to have high motivation level as well as good proficiency level of the English language. This study revealed that these 3 factors are very important to determine the anxiety level among the ESL learners. Based on the data from the interview session, the respondents shared their experience in learning to speak using English language. Most of the respondents also stated similar feedbacks as it is not contradict with the result gathered from the quantitative data. The respondents also expressed that the main barrier that make them feel anxious to speak is the fear of negative evaluation. Hence, the motivation factor also contributes as they believed that the motivation to learn the language in early age will help them to speak better. As for the language proficiency, the aspects that rose up the concern among the respondents are the vocabulary and the pronunciation. This study suggests that with appropriate teaching methodology and more effective learning environment will help the ESL learners to deal with their anxiety in speaking English language. This study will help the ESL lecturers to know in detail regarding the factors that contribute to speaking anxiety. The lecturers will have the guide to provide an action plan to curb with the problem and at the same time improvise their teaching methods.For future studies related to speaking anxiety, it is better if the reseatghers could identify effective teaching methodology or techniques on teaching speaking skills.lt is hoped that with further studies on this issue and with larger scale of respondents will further improved and bring dimensional perceptions towards the language lecturer and the ESL students.